2010
DOI: 10.1080/00914037.2010.504143
|View full text |Cite
|
Sign up to set email alerts
|

Thermoplastic Composites Based on Renewable Natural Resources: Unplasticized PVC/Olive Husk

Abstract: The current study explores the potential of eco-friendly biomaterials, namely olive husk (OH) as a reinforcing filler for PVC composite. Thus, composite-based unplasticized poly(vinyl chloride) (u PVC) and olive husk were mixed by a Brabender two-roll mill at 180 C and 25 rpm. The olive husk concentration was progressively varied from 0-20 phr. The fabricated samples were inspected with respect to their tensile properties, impact strength, thermal stability, and density and water uptake. It has been found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 12 publications
5
13
0
Order By: Relevance
“…On the other hand the dipole-dipole interactions are confirmed in Figure 2b as well, the related absorption is the carboxylic acid at 1690-1725 cm -1 and the absorption at 3627 cm -1 related the N-H from the N of the quaternary ammonium salt of the NLS and the proton of hydroxyl group involved in H-bond, one more significant peak at 3275cm -1 that is related to the OH involved in H-bond. It is worth mentioning that we observed that the XNBR vulcanizate reinforced OSW showed only H-bond formation without any ester formation 7 . The formation of ester was detected in the presence of NLS as shown in the current work.…”
Section: X-ray Photon Spectroscopymentioning
confidence: 82%
See 2 more Smart Citations
“…On the other hand the dipole-dipole interactions are confirmed in Figure 2b as well, the related absorption is the carboxylic acid at 1690-1725 cm -1 and the absorption at 3627 cm -1 related the N-H from the N of the quaternary ammonium salt of the NLS and the proton of hydroxyl group involved in H-bond, one more significant peak at 3275cm -1 that is related to the OH involved in H-bond. It is worth mentioning that we observed that the XNBR vulcanizate reinforced OSW showed only H-bond formation without any ester formation 7 . The formation of ester was detected in the presence of NLS as shown in the current work.…”
Section: X-ray Photon Spectroscopymentioning
confidence: 82%
“…The sample showed the following elements as presented in Figure 1a, carbon 6 as C 1s peak, nitrogen 7 as N 1s peak, oxygen 8 20 as Ca 2p 3/2 , Ca 2p 1/2 , Ca 2s and Ca 3s peaks. The wide-scan and high-resolution C 1s XPS spectra of the OSW is shown in Figure 1b.…”
Section: X-ray Photon Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Among them energy production, production of activated carbon, cosmetics industry, biosorbents production or animal feeding, are especially worth mentioning. OS have been also incorporated into manufacturing of WPCs, however mainly polyolefins and poly(vinyl chloride) were used as a matrices for such applications [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Referring to agro-waste materials in Jordan, wheat straw (WS) and olive pomace (OP) are two common agricultural wastes they were used as building material, burned in the open atmosphere which produces a lot of CO 2 , further it is being used to feed animals especially the wheat straw. However, recently various attempts were made by us to produce MCC from olive pomace (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18), but up to our knowledge no attempt has been made to extract MCC from the WS and. In this work MCC will be extracted from wheat straw (WS) by the removal of non-cellulosic components relying on mercerization treatment of the WS followed by hydrolysis technique.…”
Section: Introductionmentioning
confidence: 99%